PEMERINTAHAN DAERAH DALAM SISTEM OTONOMI - Johansyah, Johansyah (Faculty of Law, University of Palembang, 2018)
Local government system has connection to regional autonomy, which has been applied in Indonesia. Then before, all systems are centralized administration, then after the implementation of regional autonomy expected the region could set its own regional government of live by optimizing the existing pontential of the region. Nevertheless, there are some things remain regulated by the central government as the country’s financial affairs, religion, foreign affairs, and others, Also, local government system actually is one form of government that is efficient and effective. Because in general, the central government may not take care of all the country’s problems are so complex. On the other hand, local governments as well as the training ground and the development of democracy in a counntry life.